Community Empowerment in Tulangan District by Muhammadiyah Branch Managers - Julfah Julfah; Muhlasin Amrulloh; Vinna Anggreani; Hana Nathana Salsabila; Vallyria Mamta Aulia; Melinda Kartika Sari; Azza Hikmiawati (Proceedings of The ICECRS, 2020)
The head of the Muhammadiyah Tulangan branch is one of the Muhammadiyah branches that is still active in the Sidoarjo district. The branch office of Muhammadiyah Tulangan has several Muhammadiyah branches which are still active now, have a number of Muhammadiyah business charities, and have several excellent programs that have been formed. In the leadership of the reinforcement branch also organizes non-formal education that is held Islamic studies conducted on Sunday and also social service activities. Based on this, the purpose of this research is to know the activeness of Tulangan's Muhammadiyah branch leaders through a superior program established. This research is a field research, where in this study uses a qualitative approach which is a research step that produces data in the form of written or oral. The method used in collecting data is by using the method of observation, interviews, and documentation. While the analysis uses descriptive analysis. Descriptive analysis is analyzing data in the form of narration. Based on the analysis of existing data, there is a conclusion that the superior programs of Tulangan branch leaders in Tulangan in order to raise community welfare, overcome social problems, educate the community and overcome the problems of public awareness that is done through formal and informal education. Existing formal education that is there are schools in the auspices of Muhammadiyah in the area of ​​reinforcement. While non-formal education is held routine recitation of prayer every Sunday.